Synthesis of Eugenol Derivatives and Evaluation of their Antifungal Activity Against Fusarium solani f. sp. piperis - Maximino, Sarah C.; Dutra, Jessyca A.P.; Rodrigues, Ricardo P.; Gonçalves, Rita C.R.; Morais, Pedro A.B.; Ventura, José A.; Schuenck, Ricardo P.; Júnior, Valdemar L.; Kitagawa, Rodrigo R.; S. Borges, Warley (Current Pharmaceutical Design, 2020)
Background: Fusarium solani f. sp. piperis is a phytopathogen that causes one of the most destructive diseases in black pepper crops, resulting in significant economic and crop production losses. Consequently, the control of this fungal disease is a matter of current and relevant interest in agriculture. Objective: The objective was to synthesize eugenol derivatives with antifungal activity. Methods: In this study, using bimolecular nucleophilic substitution and click chemistry approaches, four new and three known eugenol derivatives were obtained. The eugenol derivatives were characterized and their antifungal and cytotoxic effects were evaluated. Results: Eugenol derivative 4 (2-(4-allyl-2-methoxyphenoxy)-3-chloronaphthalene-1,4-dione) was the most active against F. solani f. sp. piperis and showed acceptable cytotoxicity. Compound 4 was two-fold more effective than tebuconazole in an antifungal assay and presented similar cytotoxicity in macrophages. The in silico study of β-glucosidase suggests a potential interaction of 4 with amino acid residues by a cation-π interaction with residue Arg177 followed by a hydrogen bond with Glu596, indicating an important role in the interactions with 4, justifying the antifungal action of this compound. In addition, the cytotoxicity after metabolism was evaluated as a mimic assay with the S9 fraction in HepG2 cells. Compound 4 demonstrated maintenance of cytotoxicity, showing IC50 values of 11.18 ± 0.5 and 9.04 ± 0.2 μg mL-1 without and with the S9 fraction, respectively. In contrast, eugenol (257.9 ± 0.4 and 133.5 ± 0.8 μg mL-1), tebuconazole (34.94 ± 0.2 and 26.76 ± 0.17 μg mL-1) and especially carbendazim (251.0 ± 0.30 and 34.7 ± 0.10 μg mL-1) showed greater cytotoxicity after hepatic biotransformation. Conclusion: The results suggest that 4 is a potential candidate for use in the design of new and effective compounds that could control this pathogen.
Keywords: Antifungal